2005
DOI: 10.2466/pms.100.3c.920-924
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Suicide in the United States, 1971 to 2000

Abstract: The seasonality of suicides in the USA increased from the 1970s to the 1990s. A significant proportion of suicide variation due to the seasonal component has been reported. Noted increments in seasonal rhythms in the latter part of the 1980s and 1990s seem to support those of Warren, et al. but contradict the conclusions of diminishing drawn by Hakko, et al., Rhimer, et al., and Yip, et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
19
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 14 publications
10
19
0
3
Order By: Relevance
“…Seasonality of suicides has been shown to decrease in most [5], [8][11], but not all, countries [13], [14]. Furthermore, the amplitude of seasonal variation has repeatedly been shown to be associated with absolute suicide numbers [12], [16], which also held with the present data.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Seasonality of suicides has been shown to decrease in most [5], [8][11], but not all, countries [13], [14]. Furthermore, the amplitude of seasonal variation has repeatedly been shown to be associated with absolute suicide numbers [12], [16], which also held with the present data.…”
Section: Discussionsupporting
confidence: 87%
“…More recently, seasonality of suicide was reported to be decreasing in Finland [8], Denmark [9], the Swedish island of Gotland [10], England and Wales [11], and Switzerland [5]. Other studies found no decrease in seasonality in Italy [12], and even an increase in Australia [13] and the USA [14]. It was hypothesized that absolute suicide numbers are related to the strength of seasonality in suicides [15], which, from a mathematical point of view, is a logically consistent assumption: When the absolute suicide frequency is higher, seasonal variation increases.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the findings of Corcoran et al (2005) of a seasonal effect for men only, the results presented in the study reported here of a seasonal effect for both men and women and of an increase over time since the earlier study (Reid 1980) suggests that it may be a true findings and that the role of season is increasing in both sexes albeit still only making a small contribution. Such an evolving pattern was identified in the United States also (Bridges et al 2005). Clearly further studies over time are warranted to explore this changing pattern in Ireland and to examine possible causes, should it continue.…”
Section: Subgroup Analysismentioning
confidence: 83%
“…Recent studies using data from England and Wales [99], Hong Kong [100], Sweden [101], and Denmark [102] have demonstrated a diminishing seasonality tendency on suicides. However, this phenomenon does not apply in some other countries, such as Finland [20,39,41] and the United States [103], where a resilient seasonality pattern continues to be found for suicides or parasuicides. Overall, there might be a possibility that the contribution of season, while present, is so small that it can be irrelevant when other risk factors, such as gender and mental illnesses, are adjusted for.…”
Section: Discussionmentioning
confidence: 99%